Respuesta :

Answer:

y^2 - 10y + 25

Step-by-step explanation:

(y - 5)^2 =

(y - 5) • (y - 5)

Multiply y times y

y^2

Add 5 and 5

10

Multiply 5 and 5

25

Add these terms together

y^2 - 10y + 25

Answer: (y - 5)² = y² - 10y + 25

Concept:

There are in total three general types of parentheses-squared method:

  • (a - b)² = a² - 2ab + b²
  • (a + b)² = a² +2ab + b²
  • (a - b) (a + b) = a² - b²

Solve:

Given = (y - 5)²

Apparently, the given expression accords with (a - b)², where [y] = [a] and [5] = [b].

(a - b)² = a² - 2ab + b²

(y - 5)² = y² - 2(y)(5) + 5² = y² - 10y + 25

Hope this helps!! :)

Please let me know if you have any questions